1990
DOI: 10.1093/jmedent/27.6.1067
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Fixation: In Situ Tick (Acari: Ixodidae) Histoanatomy, Thin Sectioning of Tick Tissues, and Antigen Preservation in Mouse Spleen

Abstract: Microwave irradiation was used for the fixation of eggs, nymphs, and adult Boophilus spp. ticks. Although optimal temperatures for fixation of the different tick stages varied, heating to 58 degrees C of adult ticks submerged in either PBS or fixative was found to be sufficient. After microwave fixation, whole adult ticks, hand held, were sectioned with a sharp razor blade. The resulting sections revealed the in situ histoanatomy of the tick. Thin sections of ticks were obtained after either paraffin or polyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Carranza et al (1990) reported excellent preservation for tick tissues heated in a microwave, by using phosphate buffered saline (PBS) alone, rather than fixative.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Carranza et al (1990) reported excellent preservation for tick tissues heated in a microwave, by using phosphate buffered saline (PBS) alone, rather than fixative.…”
mentioning
confidence: 99%
“…Positive results have been reported by many workers who have used MW processing for light microscopy. Carranza et al (1990) reported excellent preservation for tick tissues heated in a microwave, by using phosphate buffered saline (PBS) alone, rather than fixative. However, since a dissecting microscope, (thus low magnification) was used, only gross anatomical structures were examined.…”
mentioning
confidence: 99%